The accuracy aspects of publications of the Directorate of Vocational High School Development in promoting the existence of the secondary vocational education through mass media - Samsul Hadi; Suyanto Suyanto; Slamet Slamet (Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
This study is an evaluation research aimed at examining the accuracy of substances, media, and publication schedules on the publications conducted by the Directorate of Vocational High School Development. The purposes of this study are: (1) to get information about the strength and weakness of the publication contexts which has become the basis of deciding the substances, media and publication schedule through mass media in order to get the publication effective and efficient to reach every level of society; (2) to get detail information about the accuracy of the using of substances, media and audiences’ habits in the implementation phase of the publication programs of the Directorate of Vocational High School Development through mass media. This research involved vocational high school communities as the samples, including the students, teachers and parents based on the stratified-cluster sampling technique. Meanwhile, the data analysis technique used was the descriptive statistic technique. In general, the result of this research shows that the substances of the publication are appropriate to public’s expectation, while the use of mass media and its publication schedule are not yet fully appropriate to achieve accuracy.